The Laboratory of Experimental Psychology: Establishing a psychological community at a Brazilian university - Cirino, Sérgio Dias; Miranda, Rodrigo Lopes; de Souza Júnior, Eustáquio José (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2013)
This paper aims to introduce the laboratory of experimental psychology as a truth-spot, as well as to investigate the social networks formed at the laboratory, in the initial implementation of the psychology degree at the Universidade Federal de Minas Gerais (UFMG). In considering the principles that a laboratory can be designed as a generator of facts/truths and, at the same time, as a support structure for the formation of academic communities, we carried out interviews with five professors from UFMG. These interviews revealed the social supports provided by the laboratory for the psychology degree at UFMG. The interviews were interpreted by means of historical information relating to both the establishment of the psychology degree and to the discussions on the higher education in the national context at that time. We found that the establishment of the laboratory of experimental psychology played a central role in the formation of the university’s psychology department, in the establishment of a degree in that discipline, and in raising the status of psychology as a profession.